Genetics of renovascular hypertension in children. Issue 10 (October 2020) - Viering, Daan H.H.M.; Chan, Melanie M.Y.; Hoogenboom, Lieke; Iancu, Daniela; de Baaij, Jeroen H.F.; Tullus, Kjell; Kleta, Robert; Bockenhauer, Detlef
Abstract : Objective: In most cases of renovascular hypertension in children, the cause is unclear. The aim of this study was to investigate genetic variation as a factor in the development of renovascular hypertension in children. Methods: In a cohort of 37 unrelated children from a single tertiary referral center, exome sequencing was performed. We assessed variants in recognized and suspected disease genes and searched for novel ones with a gene-based variant-burden analysis. Results: In the majority of patients, exome sequencing could not identify causative variants. We found a pathogenic variant in a recognized associated disease gene in five patients (three pathogenic variants in NF1, one in ELN and a deletion of chromosome 7q11.23, consistent with Williams syndrome). In two other patients, (likely) pathogenic variants were found in putative renovascular hypertension genes ( SMAD6 and GLA ), with clinical implications for both. Ten additional patients carried variants of uncertain significance (VUS) in known ( n = 4) or putative ( n = 6) renovascular hypertension disease genes. Rare variant burden analysis yielded no further candidate genes. Conclusion: Genetic contributors, such as germline mutations in NF1, ELN, 7q11.23del were present in only 5 out of 37 (14%) children with renovascular hypertension. Twelve other children (32%) had potentially causal variants identified, including a pathogenic variant in SMAD6 ; a vasculopathy gene hitherto unknown to link with renovascular hypertension. Most importantly, our data show that exome sequencing can rarely identify the cause of renovascular hypertension in nonsyndromic children. We suggest that nongenetic factors or somatic genetic variation will play a more important role. Abstract : Supplemental Digital Content is available in the text